The Human Cytomegalovirus US10 Gene Product Delays Trafficking of Major Histocompatibility Complex Class I Molecules - Furman, Margo H. (American Society for Microbiology, 2002)
Human cytomegalovirus (HCMV) US10 encodes a glycoprotein that binds to major histocompatibility complex (MHC) class I heavy chains. While expression of US10 delays the normal trafficking of MHC class I molecules out of the endoplasmic reticulum, US10 does not obviously facilitate or inhibit the action of two other HCMV-encoded MHC class I binding proteins, US2 and US11.